(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The 2022’s Global Food Security Index has reflected their concern to have affordability and safety prevail over food security globally. The author in this paper demarcates the need to make better policies and programs by the authorities in order to reduce poverty and hunger in society. The concern is made to encourage the practice of a healthy environment and protect the rights of all human beings to live with dignity and equality in this world. Moreover, emphasis is made on understanding the concept of food security. The author postulates the important role played by United Nations in working with other organizations in order to safeguard human life by providing food and nutritional security. This paper examines the need and significance of food security around the world. The focus is drawn on the factors which have led to food insecurity and how we can provide a protective sheet to the people through the practice of food security at present and for the future generation.